2021
DOI: 10.1002/jat.4205
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide alleviates apoptosis and autophagy induced by beryllium sulfate in 16HBE cells

Abstract: Beryllium and its compounds are systemic toxicants that are widely applied in many industries. Hydrogen sulfide has been found to protect cells. The present study aimed to determine the protective mechanisms involved in hydrogen sulfide treatment of 16HBE cells following beryllium sulfate-induced injury. 16HBE cells were treated with beryllium sulfate doses ranging between 0 and 300 μM BeSO 4 .Additionally, 16HBE cells were subjected to pretreatment with either a 300 μM dose of sodium hydrosulfide (a hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…For example, Yoshida et al (2019) reported that cigarette smoke exposure can be mediated by NCOA4, while ferritinophagy promotes unstable iron accumulation, lipid peroxidation, and ferroptosis in human bronchial epithelial cells, which participates in COPDs. In fact, we observed increased intracellular free H 2 S is a third endogenous signaling molecule, which contributes to physiological and pathological responses of various organs through antioxidant defense, anti-inflammation, antiautophagy, and inhibiting ferroptosis (Citi et al, 2018;Jin et al, 2020;Y. P. Liu, Yuan, et al, 2022;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…For example, Yoshida et al (2019) reported that cigarette smoke exposure can be mediated by NCOA4, while ferritinophagy promotes unstable iron accumulation, lipid peroxidation, and ferroptosis in human bronchial epithelial cells, which participates in COPDs. In fact, we observed increased intracellular free H 2 S is a third endogenous signaling molecule, which contributes to physiological and pathological responses of various organs through antioxidant defense, anti-inflammation, antiautophagy, and inhibiting ferroptosis (Citi et al, 2018;Jin et al, 2020;Y. P. Liu, Yuan, et al, 2022;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…However, the role of ferroptosis and ferritinophagy in beryllium disease remains unclear. Intriguingly, our previous results found that BeSO 4 induced oxidative damage, apoptosis, and autophagy in 16HBE cells (Y. P. Liu, Yuan, et al, 2022), as well as PTGS2, a biomarker of ferroptosis was upregulated in 16HBE cells treated with 150 μM BeSO 4 (Yi et al, 2021). In this study, we determine the effect of BeSO 4 on the occurrence of ferroptosis in 16HBE cells with or without the intervention of DFO (a specific inhibitor of ferroptosis) and then preliminarily explored its mechanism (Miao et al, 2022;J.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A cohort study of workers at seven beryllium processing plants showed that workers exposed to ≥10 μg/m 3 (0.001 μmol/L) beryllium had higher rates of lung cancer, urinary tract cancer, COPD, and cor pulmonale than workers with lower exposures (Schubauer‐Berigan et al, 2011). Many in vitro and in vivo studies have found that beryllium exposure induces inflammation, oxidative stress, apoptosis, and autophagy (Liu et al, 2021; Yi et al, 2020). Beryllium has been shown to interfere with cell homeostasis, generate excessive reactive oxygen species (ROS), and induce mitochondrial dysfunction, leading to pulmonary disease (Ding et al, 2000).…”
Section: Introductionmentioning
confidence: 99%